Potential Role of Nanostructured Lipid Carrier as Cutting-Edge Approach for Drug Delivery of Nonsteroidal Anti-Inflammatory Drugs - Zahoor, Ishrat; Singh, Sukhbir; Sharma, Neelam; Wani, Shahid Nazir; Kishore, Ladli (Scripta Medica, 2025)
The majority of nonsteroidal anti-inflammatory drugs (NSAIDs) are categorised as Biopharmaceutics Classification System (BCS) class II or IV drugs, indicate their limited solubility and permeability. The nanostructured lipid carriers (NLCs) can be utilised in drug delivery of NSAIDs to decrease adverse effects and create controlled-release oral formulations. The utilisation of NLCs in transdermal and topical formulations of NSAIDs has demonstrated better efficacy in alleviating inflammation and pain, both at the site of application and throughout the body. This review offers concise insights into the characteristics and mode of action of NSAIDs in the inflammatory cascade. The current review provides a complete overview of the advanced functions of NLCs in delivering NSAIDs through various routes of administrations, including buccal, cutaneous, transdermal, ocular, oral controlled, parenteral and pulmonary routes. To accomplish this objective, an extensive literature search was conducted utilising the ScienceDirect, PubMed and Google Scholar databases. A systematic review was undertaken using scholarly publications published in peer-reviewed journals from 2000 to 2024. Research has established that NLCs possess considerable potential in offering diverse benefits in the delivery of NSAIDs. These benefits include improved skin penetration and precise targeting when applied topically, enhanced drug retention on the corneal surface and effective transport across ocular barriers when administered to the eyes, extended drug residence period in the lungs and increased diffusion mobility when administered through the pulmonary route, as well as prolonged and sustained duration of action when administered buccally, parenterally, or orally. This analysis emphasises the considerable capacity of NLCs to efficiently transport NSAIDs while reducing their negative impacts in the management of inflammatory diseases.
Keywords: Drug administration, buccal; Drug delivery systems; Inflammation; Anti-inflammatory agents, non-steroidal; Nanostructured lipid carriers; Administration, ophthalmic; Administration, cutaneous